Numerical heat transfer simulation system based on Lagrangian particle mathematical model and SSPH algorithm. - Dan Fang; Conghui Xiong; Wei Yu (PLoS ONE)
With the continuous promotion and development of national industrialization, the performance control of precision casting and mechanical structures has become increasingly important. The traditional craftsmanship in the foundry industry relies on experience and trial-and-error method, resulting in high cost and long trial production cycles. A numerical heat transfer simulation system is proposed based on the Lagrangian particle mathematical model and optimized numerical heat transfer simulation algorithm. The simulation results showed that the simulation accuracy of the system was as high as 99.1%. The simulation time was stable at 434 ms, with CPU usage and memory usage controlled at 23% and 18%, respectively, surpassing the comparison system. The calculated results do not show any non-physical oscillations, ensuring the authenticity and reliability of simulation results. The results indicate that the numerical heat transfer simulation system provides an efficient, accurate, and low resource consuming simulation tool for the foundry industry, which promotes the rapid development of the manufacturing industry.